The decline of bone conduction in chronic otitis media – Retrospective analysis of 177 surgical cases - Damaso, Guedes (2017)
Objectives: Assess whether chronic otitis media (COM) accelerates deterioration of bone conduction. Study design: Retrospective study.Materials and methods: From 688 patients operated on for COM (years 2009-2013) at Hospital São José, 212 were randomly analyzed and exclusion criteria were applied resulting in 177 patients. We compare average tonal bone conduction threshold (ATBCT) of the sample, with results of the sample of the british population studied by Davis et al. in 1989. Age, gender, type of otorrhea and type of COM were registered. Statistical analysis was conducted using SPSS 22.0®.Results: Applying binomial proportion test, by comparing the results from our study and Davis et al. study, we verified a statistically significant difference in all age groups (except 71-80 years) for the occurrence of ATBCT≥20. There was also a statistically significant difference for the occurrence of ATBCT≥40, but only in three age groups.Conclusions: COM increases deterioration of bone conduction.